Improving Self-Efficacy of Gout Arthritis Sufferers with Self-Help Group - Cornelia Fransiska Sandehang; Dian Handayani; Yati Sri Hayati; Niko Dima Kristianingrum; Kumboyono Kumboyono; Annisa Wuri Kartika (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Gouty arthritis can cause severe pain and other symptoms, that interfere with the activities and enthusiasm of the participants in carrying out disease treatment programs. Therefore, efforts are needed to increase the self-efficacy of sufferers. Self-Help Groups are a type of group therapy that can help exchange experiences and information about disease care and increase emotional support that motivates sufferers to gain self-confidence. This study aims to analyze the effect of implementing a self-help group on the self-efficacy of people with gouty arthritis. This study used a quasi-experimental design with pretests and posttests in the control group. The total sampling technique collected 60 people with gouty arthritis from the Dau Public Health Center in Malang Regency. Data was collected using the Arthritis Self-Efficacy Scale (ASES) questionnaire to assess the respondents' self-efficacy before and after the intervention. The data analysis process used a statistical approach. Paired Sample t-test and Independent Sample t-test by performing the normality and homogeneity tests with Shapiro-Wilk. There was a significant difference in self-efficacy of people with gouty arthritis after participating in a self-help group, according to the findings. It is recommended that the self-help group become a group activity that continues to be carried out for patients with chronic diseases at the public health centers. Abstrak: Gout arthritis dapat mengakibatkan nyeri hebat dan gejala lain, yang mengganggu aktivitas dan semangat penderita dalam menjalankan program perawatan penyakit. Maka dibutuhkan upaya untuk meningkatkan efikasi diri para penderita. Self Help Group merupakan terapi kelompok yang dapat memfasilitasi terjadinya proses bertukar pengalaman serta informasi mengenai perawatan penyakit, dan meningkatkan dukungan emosional yang memotivasi para penderita, sehingga dapat meningkatkan keyakinan akan kemampuan diri. Penelitian ini bertujuan untuk menganalisis pengaruh pelaksanaan Self Help Group terhadap efikasi diri penderita Gout Arthritis. Penelitian ini menggunakan desain quasy experimen, dengan pretest dan posttest pada kelompok kontrol. Sampel penelitian ini adalah 60 orang penderita Gout Arthritis di Puskesmas Dau Kabupaten Malang, yang diperoleh dengan teknik total sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner The Arthritis Self-Efficacy Scale (ASES) untuk menilai efikasi diri responden sebelum dan sesudah dilakukan intervensi. Proses analisis data menggunakan pendekatan statistik Paired Sample t-test dan Independent Sample t-test dengan terlebih dahulu dilakukan uji normalitas menggunakan Saphiro Wilk dan uji homogenitas. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan pada efikasi diri penderita Gout Arthritis setelah dilaksanakan Self Help Group. Direkomendasikan agar Self Help Group dapat menjadi aktivitas kelompok yang terus dilaksanakan pada penderita penyakit kronis di Puskesmas.